A novel volute design for reducing radial force in pump and PAT. Issue 4 (March 2019) - Arani, Hamed Alemi; Fathi, Mohammad; Raisee, Mehrdad; Nourbakhsh, Seyed Ahamd
Abstract: In the current paper a novel volute design is proposed to reduce the radial force of a low specific speed centrifugal pump in both direct and reverse modes. First, the fluid flow in the pump in both modes was simulated by utilizing commercial CFD software. For evaluation of unknown Reynolds-Stresses, the k - ω turbulence model was employed. The nonlinear convective terms in all transport equations were approximated by the second-order upwind scheme. The unstructured computation grid with 1.75×10 6 cells was used for the computation. The numerical results were verified against the measured data and acceptable agreement between them was found. Numerical results showed that changing the operating mode of a pump from direct to reverse increases the flowrate, head and power in the BEP but deteriorates the radial force. Therefore, a novel volute based on BEP flowrate of PAT was proposed. In pump mode, it was found that although this novel design decreases the efficiency in low flowrates slightly, it increases the head and efficiency in high flowrates considerably. Interestingly, the radial force is decreased significantly and the point of minimum radial force is shifted to 125% of BEP flowrate. The comparison of PAT performance with the original volute and the novel one revealed that the new design leads to lower head and power in all flowrates. However, this design provides more uniform pressure distribution around the impeller periphery and thus reduces the radial force.